It’s Not Just About the Game: A Study on Attitudes and Motivation of Malaysian Secondary Sports School Students in East Malaysia towards Learning English as a Second Language - Nursyaheedah, Muhammad Isa; Noor Azlinda, Zainal Abidin; Nabila, Abdul Malek; Mohamad Hazeem, Mohmad Sidik; Safirul Azli, Abu Bakar (EDP Sciences, 2018)
In the past few years, Malaysian athletes have gained international recognition with their impressive, world-record breaking accomplishments. As a result of this, Malaysian athletes are finding themselves being interviewed and giving speeches at local and international events. For professional athletes, there is a need and a duty to be able to communicate their stories and experiences as well as giving real insight and opinions about their performances, confidently, to both local and global audiences. In addressing these audiences, it is important for these professional athletes to be confident and are able to converse well using the English language, especially so when addressing a global audience. However, some Malaysian athletes are facing difficulties in communicating confidently and coherently, especially in English. It is a recognised and acknowledged skill gap in which is believed should be tackled during the formative school years. It is possible that the skill gap stems from a lack of motivation and poor attitude beginning from secondary school. This paper discusses the findings of a study undertaken to investigate these issues further by carrying out a questionnaire survey on the attitudes and motivation of Malaysian secondary sports school students in East Malaysia towards learning English as a second language. The study reveals an overall positive attitude towards learning English by the sports students. In addition, the findings reveal that the sports school students are extrinsically and intrinsically motivated in learning English. The study concludes with recommendations for future research and is expected to make a contribution to the literature of attitudes and motivation especially for but not limited to secondary sports school students.